(untitled) (Kairaranga, 2020)
This paper examines the multi-component use of visual supports, namely visual schedules and video modelling, to achieve the vocational goal of making a sandwich independently for a 16-year old girl with autism. This practice approach was informed by both the three step process from the National Professional Development Centre (The NPDC Model, n.d.) as well as from a Kaupapa Maori culturally-responsive perspective - He Ritenga Whaimo hio (Macfarlane & Macfarlane, 2013). Relevant research (tika) and underpinning theories of autism were considered, family voice and priorities collected (aroha), and a teaching plan developed, implemented and evaluated (pono) to achieve the long-term goal of increasing a young woman’s independence. The intervention was led by the author of this paper supporting the Special School classroom teacher, teacher-aides, parents and the student directly. The successes and challenges of this intervention were monitored and will be critically discussed in this practice paper.